Natural abilities? Work processes in the case of the employees at a chemical factory in argentina Cecilia - Cecilia Anigstein (Punto Género, 2013)
This research explores those social proceses in which women’s subalternity at work is founded. By using a qualitative methodology. The case study were branche of chemical industrie placed in the Gran Buenos Aires, Argentina. This research approaches different perspectives such as the social relation between sexes, it considers the way by which the construction of technical qualification involves the naturalization of women’s productive skills at the convey belt. Our purpose is to contribute to a set of debates about the particularlities of the social experience and the type of relation that women establish with their work, in the case of unskilled industry workers of contemporary Latin-American societies.